2007
DOI: 10.1098/rsif.2007.1063
|View full text |Cite
|
Sign up to set email alerts
|

The interfacial structure and Young's modulus of peptide films having switchable mechanical properties

Abstract: We report the structure and Young's modulus of switchable films formed by peptide selfassembly at the air-water interface. Peptide surfactant AM1 forms an interfacial film that can be switched, reversibly, from a high-to low-elasticity state, with rapid loss of emulsion and foam stability. Using neutron reflectometry, we find that the AM1 film comprises a thin (approx. 15 Å) layer of ordered peptide in both states, confirming that it is possible to drastically alter the mechanical properties of an interfacial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
93
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(112 citation statements)
references
References 52 publications
18
93
1
Order By: Relevance
“…Since the late 1990s, its use in the study of different biointerfacial phenomena has also been reported. The biomolecular systems that have so far been studied include proteins (Lu et al ,d, 1999a(Lu et al ,b,c, 2003bSu et al 1998aSu et al ,b,c, 1999Su et al , 2000Fragneto et al 2000b;Holt et al 2000;Nylander et al 2001;Armstrong et al, 2004;Cooper et al 2005;Xu et al 2006bXu et al , 2007Xu et al , 2008Pan et al 2008), peptides (Holt et al 2000;Lu et al 2003aLu et al , 2004Lad et al 2007;Middelberg et al 2008;Zhao et al 2009), biosurfactants (Follows et al 2007) and lipid bilayers (Fragneto et al 2000a. A number of neutron reflection studies have also focused on interfacial interactions from binary mixtures of protein/surfactant (Lu et al 1998a,b;Green et al 2000aGreen et al ,b, 2001, protein or peptide/lipid (Schmidt et al 1992;Lu et al 2001;Miano et al 2007;Valincius et al 2008), protein/polymer Hollmann et al 2007Hollmann et al , 2008; Ganzevles et al 2008), DNA/polymer (Zhao et al 2008a), DNA/surfactant (Zhang et al 2008) and DNA/ lipid (Wu et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Since the late 1990s, its use in the study of different biointerfacial phenomena has also been reported. The biomolecular systems that have so far been studied include proteins (Lu et al ,d, 1999a(Lu et al ,b,c, 2003bSu et al 1998aSu et al ,b,c, 1999Su et al , 2000Fragneto et al 2000b;Holt et al 2000;Nylander et al 2001;Armstrong et al, 2004;Cooper et al 2005;Xu et al 2006bXu et al , 2007Xu et al , 2008Pan et al 2008), peptides (Holt et al 2000;Lu et al 2003aLu et al , 2004Lad et al 2007;Middelberg et al 2008;Zhao et al 2009), biosurfactants (Follows et al 2007) and lipid bilayers (Fragneto et al 2000a. A number of neutron reflection studies have also focused on interfacial interactions from binary mixtures of protein/surfactant (Lu et al 1998a,b;Green et al 2000aGreen et al ,b, 2001, protein or peptide/lipid (Schmidt et al 1992;Lu et al 2001;Miano et al 2007;Valincius et al 2008), protein/polymer Hollmann et al 2007Hollmann et al , 2008; Ganzevles et al 2008), DNA/polymer (Zhao et al 2008a), DNA/surfactant (Zhang et al 2008) and DNA/ lipid (Wu et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…While the presence of the additional aspartate residue (with its negative charge) has the effect of shifting the theoretical pI slightly from 7.3 for DAMP1 to 6.7 for DAMP4, our earlier study of the foaming and film-forming properties of DAMP1 and DAMP4 [16] indicated that their behaviours were not significantly influenced by the presence of these additional residues. DAMP1 and DAMP4 are based on the surface-active peptide AM1 [17], which was designed to adsorb as a single a-helix at the air-water or oil-water interface (monolayer structure was confirmed by neutron reflectometry [18]). It is expected that DAMP1 will behave similarly.…”
Section: Introductionmentioning
confidence: 99%
“…This peptide adsorbed to the air-water interface and lowered interfacial tension as a function of molecular charge. 194 At low pH, where glutamate residues are partially neutralised, Lac21E readily adsorbed to the interface, lowering interfacial tension and forming an interfacial film. Conversely, at high pH, where glutamate residues are deprotonated, peptide desorbed from the interface and film formation was lost.…”
Section: Surfactantsmentioning
confidence: 99%